Regional E-Infrastructure and Services for Research and Education in EAP Countries - Petru BOGATENCOV; Grigore SECRIERU (Eastern European Journal of Regional Studies)
In the paper considering approaches and solutions for development of modern regional e-Infrastructure resources for providing specific services to the research and educational communities in countries supported by European Eastern Partnership Programme. Over the past several years the dependence of research and education on access to high-speed networking infrastructures, to large-scale computing and other e-Infrastructures’ services is rapidly increasing. e-Infrastructure designates a new generation of integrated ICT based resources, services and is widely considered as a key enabler for scientific and social development. Such infrastructures represent a distributed medium based on high-bandwidth networks, distributed Grid computing, High Performance Computing (HPC), scientific Cloud resources and respective data repositories. The focus is made on describing the various services that are deploying in the Eastern Partnership countries to support educational and research activities in universities and research centers. Argued importance of developing of Research and Educational networks as a key e-Infrastructures’ enables. Described expected outcomes of regional projects supported by European Commission in the area on regional infrastructures and modern services deployment for research and education.